Pyroptosis in asthma: inflammatory phenotypes, immune and non-immune cells, and novel treatment approaches - Hao, Yuqiu; Wang, Wenrui; Zhang, Lin; Li, Wei (Frontiers in Pharmacology, 2024)
Pyroptosis is a form of inflammatory programmed cell death, and is activated by pathogen infections or endogenous danger signals. The canonical pyroptosis process is characterized by the inflammasome (typically NLRP3)-mediated activation of caspase-1, which in turn cleaves and activates IL-1β and IL-18, as well as gasdermin D, which is a pore-forming executor protein, leading to cell membrane rupture, and the release of proinflammatory cytokines and damage-associated molecular pattern molecules. Pyroptosis is considered a part of the innate immune response. A certain level of pyroptosis can help eliminate pathogenic microorganisms, but excessive pyroptosis can lead to persistent inflammatory responses, and cause tissue damage. In recent years, pyroptosis has emerged as a crucial contributor to the development of chronic inflammatory respiratory diseases, such as asthma. The present study reviews the involvement of pyroptosis in the development of asthma, in terms of its role in different inflammatory phenotypes of the disease, and its influence on various immune and non-immune cells in the airway. In addition, the potential therapeutic value of targeting pyroptosis for the treatment of specific phenotypes of asthma is discussed.